ZOMBIE COMPANIES IN THE CONTEXT OF STATE- OWNED ENTERPRISES IN INDONESIA - Elazhari Elazhari; Khairuddin Tampubolon; Barham Siregar; Ramadha Yanti Parinduri; Boby Indra Prayoga (International Journal of Artificial Intelligence Research, 2022)
This paper discusses “zombie” companies in the context of state- owned companies in Indonesia. Specifically, we will examine the factors that determine them to become a “zombie” company. In addition, we will examine the impact of their existence on the economy. Using a sample of 159 Indonesian state-owned companies from 2010 to 2020, we find that Indonesian state-owned companies are indicated to have zombie companies. Their existence is significantly determined by internal factors rather than external factors. Dominant external factors are significant when tested simultaneously with internal factors. In addition, we also find that their presence has a significant negative impact on economic growth and national productivity. Therefore, the government, as well as controlling the company, is expected to be able to immediately overcome their existence, which can be done by restructuring the company or if possible liquidating them. Their existence not only harms themselves, but also harms other companies, and can even harm the national economy.